Opioids Regulate the Immune System: Focusing on Macrophages and Their Organelles - Wen, Shaohua; Jiang, Yuan; Liang, Shuang; Cheng, Zhigang; Zhu, Xiaoyan; Guo, Qulian (Frontiers in Pharmacology, 2022)
Opioids are the most widely used analgesics and therefore have often been the focus of pharmacological research. Macrophages are the most plastic cells in the hematopoietic system. They show great functional diversity in various organism tissues and are an important consideration for the study of phagocytosis, cellular immunity, and molecular immunology. The expression of opioid receptors in macrophages indicates that opioid drugs act on macrophages and regulate their functions. This article reviewed the collection of research on effects of opioids on macrophage function. Studies show that opioids, both endogenous and exogenous, can affect the function of macrophages, effecting their proliferation, chemotaxis, transport, phagocytosis, expression of cytokines and chemokine receptors, synthesis and secretion of cytokines, polarization, and apoptosis. Many of these effects are closely associated with mitochondrial function and functions of other organelles in macrophages. Therefore, in depth research into effects of opioids on macrophage organelles may lead to some interesting new discoveries. In view of the important role of macrophages in HIV infection and tumor progression, this review also discusses effects of opioids on macrophages in these two pathological conditions.